Preparation and characterization of adsorptive carbonized corncob for elimination of sulfur from sulfurized n-hexane - Oday, Yousuf; Aljendeel, Haider; Nidhal Shareef, Zaid (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The present study is conducted to investigate the adsorption desulfurization process for eliminating sulfur from a simulated fuel within a sulfur content range similar to what exists in typical naphtha streams. The model oil, n-hexane, was sulfurized with dibenzothiophene (DBT), which is the most complex form of sulfur constituents in fuels. Corncob, a natural biomass waste material, was utilized to accomplish the adsorption remedy of sulfur. The carbonization process took place at 500 °C. FTIR, SEM, XRD, AFM, and BET-surface area facilitated a comprehensive characterization of carbonized corncob (CC) adsorbent. The results showed that the corncob sample has homogeneous surfaces and relatively analogous active positions. The CC adsorbent was utilized to adsorb sulfur in its DBT configuration from the sulfurized fuel (n-hexane). Certain adsorption factors of temperature, contacting time, and adsorbent dosage were examined to select the most appropriate adsorption conditions. After that, the chosen conditions were employed to adsorb various sulfur concentrations. For the same initial concentration of sulfur of 400 ppm, the removal attained 75% at favorable parameters of 60°C, 30 min, and 3g L-1, respectively. The efficiency of sulfur removal was substantially augmented with the reduction of the initial sulfur content. Thus, it attained more than 79 % when the original concentration of sulfur in the n-hexane was maintained in the range of 100 ppm. The results perfectly coincided with the Langmuir model of adsorption isotherms. The thermodynamics of the desulfurization adsorption process reflected that the adsorption is associated with an endothermic event. The estimated standard enthalpy changes were 6.34 kJ mol-1. The adsorption was spontaneous over the employed temperature range of 30 – 60°C.